2009
DOI: 10.1016/j.infsof.2008.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Models of motivation in software engineering

Abstract: Original article can be found at : http://www.sciencedirect.com/ Copyright Elsevier [Full text of this article is not available in the UHRA]Motivation in software engineering is recognized as a key success factor for software projects, but although there are many papers written about motivation in software engineering, the field lacks a comprehensive overview of the area. In particular, several models of motivation have been proposed, but they either rely heavily on one particular model (the job characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
98
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(116 citation statements)
references
References 84 publications
3
98
1
4
Order By: Relevance
“…These individual differences could rely, among other factors, on competences (Sharp, Baddoo, Beecham, Tracy, & Robinson, 2009;Turley & Bieman, 1995). Although soft ware practitioners through their competences are the enablers of the Knowledge Society (Hernández López, Colomo Palacios, García Crespo, & Soto Acosta 2010), since they provide knowledge workers with the tool to perform their work, inadequate verification of soft ware engineers' competences is usually one of the main problems within software development projects (McConnell, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…These individual differences could rely, among other factors, on competences (Sharp, Baddoo, Beecham, Tracy, & Robinson, 2009;Turley & Bieman, 1995). Although soft ware practitioners through their competences are the enablers of the Knowledge Society (Hernández López, Colomo Palacios, García Crespo, & Soto Acosta 2010), since they provide knowledge workers with the tool to perform their work, inadequate verification of soft ware engineers' competences is usually one of the main problems within software development projects (McConnell, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Software engineers' motivation has received much systematic attention [5,6,7]. Motivation is moderated by complex socio-cognitive factors, including the cultural context with its value system and individual personal characteristics [6].…”
Section: Related Workmentioning
confidence: 99%
“…Motivation is moderated by complex socio-cognitive factors, including the cultural context with its value system and individual personal characteristics [6]. Values form an important component in motivation [8], and, thus influence performance and overall work experience.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, there are several software productivity factors identified in literature: motivation (Boehm, 1987;Beecham, Baddoo, Hall, Robinson, & Sharp, 2008;Sharp, Baddoo, Beecham, Hall, & Robinson, 2009), process (Boehm, 1987) and process design and coordination issues (Chiang &Mookerjee, 2004), complexity or a size of a project (Scacchi, 1995;Boehm, 1987Boehm, , 1981, reuse of software artifacts (Lim, 2002;Boehm, 2002), communication demands regarding to team size (Scacchi, 1995;Blackburn, Scudder, & Van Wassenhove, 2002). Based on the research surveyed in this paper, Figure 1 shows several productivity factors identified for software development.…”
Section: Productivitymentioning
confidence: 99%